HUBUNGAN REAKTIFITAS UJI TUSUK DENGAN KADAR IMUNOGLOBULIN (IG) E DALAM SERUM PENDERITA DERMATITIS ATOPIK - Kariosentono, Harijono (Jurnal Kedokteran YARSI, 2005)
Skin prick test is an in vivo examination performed on the allergy suspected patients to one or more common allergens including atopic dermatitis. Atopic dermatitis (AD) is a chronic recurrent inflammatory skin disease commonly associated with an increase of IgE and a family history of atopic disease. The aim of the study was to learn the correlation between the rates of skin prick test response and the level of IgE in the serum of atopic dermatitis patients. The post test only design was control group design was, 18 AD patients and 12 individuals as the control group. The result indicated that a significant difference was observed between the reactivity of the skin prick test and the level of either IgE total or IgE specific. In conclusion a positive correlation was shown between the skin prick test and the level of IgE on AD patients employed involving.